ANALISIS KEBUTUHAN KONSUMEN SEBAGAI STRATEGI DALAM MENINGKATKAN OMSET USAHA RITEL - Rifa'i, Moh (IZZI: Jurnal Ekonomi Islam, 2021)
Analysis of consumer needs is an effective strategy in order to increase retail business incomes. Those needs have to get an attention from business managers in particular, by knowing and understanding how the strategy for analyzing consumer needs can be implemented effectively and efficiently, so that it can do authentic work that contributes toward increasing of incomes and profits. The research method used is the library method, so the researcher studies theoretically, utilizing the method of collecting data through reviewing the material available in the library both manually and digitally such as books, research results, articles, notes, and journals related. With specific steps, record the findings regarding the analysis of consumer needs, integrate all findings, whether theory or new findings, analyze findings from various readings, and critique, provide critical ideas in the results of research on previous discourses. The results suggest that the analysis of consumer needs can provide a positive contribution to increasing the volume of retail store revenue which can be implemented by utilizing the QFD (Quality Function Deployment) method and the Kano method which has positive implications giving added value to prioritizing product design, developing business strategies, knowing how and what specific customer needs, maintain customer loyalty, the terms of goods and services are more understandable, and customer satisfaction is combined with the spread of quality functions